Prospective Multicenter Comparison of Open and Robotic Radical Prostatectomy: The PROST-QA/RP2 Consortium. Issue 1 (26th January 2022) - Chang, Peter; Wagner, Andrew A.; Regan, Meredith M.; Smith, Joseph A.; Saigal, Christopher S.; Litwin, Mark S.; Hu, Jim C.; Cooperberg, Matthew R.; Carroll, Peter R.; Klein, Eric A.; Kibel, Adam S.; Andriole, Gerald L.; et al.
Abstract : Purpose: Our goal was to evaluate the comparative effectiveness of robot-assisted laparoscopic prostatectomy (RALP) and open radical prostatectomy (ORP) in a multicenter study. Materials and Methods: We evaluated men with localized prostate cancer at 11 high-volume academic medical centers in the United States from the PROST-QA (2003–2006) and the PROST-QA/RP2 cohorts (2010–2013) with a pre-specified goal of comparing RALP (549) and ORP (545). We measured longitudinal patient-reported health-related quality of life (HRQOL) at pre-treatment and at 2, 6, 12, and 24 months, and pathological and perioperative outcomes/complications. Results: Demographics, cancer characteristics, and margin status were similar between surgical approaches. ORP subjects were more likely to undergo lymphadenectomy (89% vs 47%; p <0.01) and nerve sparing (94% vs 89%; p <0.01). RALP vs ORP subjects experienced less mean intraoperative blood loss (192 vs 805 mL; p <0.01), shorter mean hospital stay (1.6 vs 2.1 days; p <0.01), and fewer blood transfusions (1% vs 4%; p <0.01), wound infections (2% vs 4%; p=0.02), other infections (1% vs 4%; p <0.01), deep venous thromboses (0.5% vs 2%; p=0.04), and bladder neck contractures requiring dilation (1.6% vs 8.3%; p <0.01). RALP subjects reported less pain (p=0.04), less activity interference (p <0.01) and higher incision satisfaction (p <0.01). Surgical approach (RALP vs ORP) was not a significant predictor of longitudinal HRQOL change in any HRQOL domain. Conclusions: In high-volume academic centers, RALP and ORP patients may expect similar long-term HRQOL outcomes. Overall, RALP patients have less pain, shorter hospital stays, and fewer post-surgical complications such as blood transfusions, infections, deep venous thromboses, and bladder neck contractures.